Fanconi anemia genes in lung adenocarcinoma- a pathway-wide study on cancer susceptibility. Issue 1 (December 2016) - Yang, Shi-Yi; Hsiung, Chia-Ni; Li, Yao-Jen; Chang, Gee-Chen; Tsai, Ying-Huang; Chen, Kuan-Yu; Huang, Ming-Shyan; Su, Wu-Chou; Chen, Yuh-Min; Hsiung, Chao; Yang, Pan-Chyr; Chen, Chien-Jen; et al.
Abstract Background Carcinogens in cigarette smoke can induce the formation of DNA-DNA cross-links, which are repaired by the Fanconi anemia (FA) pathway, and it is tempting to speculate that this pathway is involved in lung tumorigenesis. This study is to determine whether genetic polymorphism of the FA genes is associated with an elevated risk of lung adenocarcinoma, and whether the association between genotypes and risk is modified by exposure to cigarette smoke. Methods This case–control study genotyped 53 single-nucleotide polymorphisms (SNPs) in FA genes in 709 patients (354 males and 355 females) with lung adenocarcinoma and in 726 cancer-free individuals (339 males and 387 females). Genotypic frequencies of SNPs were compared between cases and controls to identify important FA genes associated with cancer susceptibility. Joint effects in determining cancer risk contributed by genes and smoking-related risk factors and by multiple genes involved in different FA subpathways were evaluated by multivariate regression analysis and stratified analysis. All analyses were performed on males and females separately, and the comparison of results was considered a way of examining the validity of study findings. Results Lung adenocarcinomas in both male and female patients were associated with (a) genotypic polymorphisms of FANCC and FANCD1; (b) a combined effect of harboring a higher number of high-risk genotypes and smoking/passive smoking; (c) specific interactions of multiple genes, proteins encoded by which have been known to work jointly within the FA pathway. Conclusions Genetic polymorphism of the FA genes is associated with inter-individual susceptibility to lung adenocarcinoma.